Response to: “Challenges in DPYD Test Implementation in Patients Treated with Fluoropyirimidines, is DPYD Genotype Arriving on Time?” [Response to Letter] - Montrasio C; Cheli S; Clementi E (Pharmacogenomics and Personalized Medicine, 2024)
Cristina Montrasio,1 Stefania Cheli,1 Emilio Clementi2,3 1Unit of Clinical Pharmacology, ASST Fatebenefratelli Sacco, L. Sacco University Hospital, Milan, Italy; 2Clinical Pharmacology Unit, Department of Biomedical and Clinical Sciences, L. Sacco University Hospital, Università degli Studi di Milano, Milan, Italy; 3Scientific Institute IRCCS Eugenio Medea, Bosisio Parini, ItalyCorrespondence: Cristina Montrasio, Unit of Clinical Pharmacology, Department of Laboratory Medicine, ASST Fatebenefratelli-Sacco, Milan, Italy, Email cristina.montrasio@asst-fbf-sacco.it